Production and molecular characterization of bread wheat lines with reduced amount of α-type gliadins - Francesco Camerlengo (BMC Plant Biology, 2017)
Abstract Background Among wheat gluten proteins, the α-type gliadins are the major responsible for celiac disease, an autoimmune disorder that affects about 1% of the world population. In fact, these proteins contain several toxic and immunogenic epitopes that trigger the onset of the disease. The α-type gliadins are a multigene family, encoded by genes located at the complex Gli-2 loci. Results Here, three bread wheat deletion lines (Gli-A2, Gli-D2 and Gli-A2/Gli-D2) at the Gli-2 loci were generated by the introgression in the bread wheat cultivar Pegaso of natural mutations, detected in different bread wheat cultivars. The molecular characterization of these lines allowed the isolation of 49 unique expressed genes coding α-type gliadins, that were assigned to each of the three Gli-2 loci. The number and the amount of α-type gliadin transcripts were drastically reduced in the deletion lines. In particular, the line Gli-A2/Gli-D2 contained only 12 active α-type gliadin genes (−75.6% respect to the cv. Pegaso) and a minor level of transcripts (−80% compared to cv. Pegaso). Compensatory pleiotropic effects were observed in the two other classes of gliadins (ω- and γ-gliadins) either at gene expression or protein levels. Although the comparative analysis of the deduced amino acid sequences highlighted the typical structural features of α-type gliadin proteins, substantial differences were displayed among the 49 proteins for the presence of toxic and immunogenic epitopes. Conclusion The deletion line Gli-A2/Gli-D2 did not contain the 33-mer peptide, one of the major epitopes triggering the celiac disease, representing an interesting material to develop less “toxic” wheat varieties.